Difference between revisions of "009B Sample Midterm 3, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">Evaluate the integral: ::<math>\int \sin (\ln x)~dx.</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations:   |- |'...")
 
Line 1: Line 1:
<span class="exam">Evaluate the integral:
+
<span class="exam"> The rate of reaction to a drug is given by:
  
::<math>\int \sin (\ln x)~dx.</math>
+
::<math>r'(t)=2t^2e^{-t}</math>
 +
 
 +
<span class="exam">where &nbsp;<math style="vertical-align: 0px">t</math>&nbsp; is the number of hours since the drug was administered.
 +
 
 +
<span class="exam">Find the total reaction to the drug from &nbsp;<math style="vertical-align: -1px">t=1</math>&nbsp; to &nbsp;<math style="vertical-align: 0px">t=6.</math>
  
  
Line 7: Line 11:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int vdu.</math>
+
|If we calculate &nbsp;<math style="vertical-align: -14px">\int_a^b r'(t)~dt,</math>&nbsp; what are we calculating?
 
|-
 
|-
|'''2.''' How could we break up <math style="vertical-align: -5px">\sin (\ln x)~dx</math> into <math style="vertical-align: -1px">u</math> and <math style="vertical-align: -1px">dv?</math>
+
|
 +
&nbsp; &nbsp; &nbsp; &nbsp; We are calculating &nbsp;<math style="vertical-align: -5px">r(b)-r(a).</math>&nbsp; This is the total reaction to the 
 
|-
 
|-
 
|
 
|
::Notice that <math style="vertical-align: -5px">\sin (\ln x)</math> is one term. So, we need to let <math style="vertical-align: -5px">u=\sin (\ln x)</math> and <math style="vertical-align: -1px">dv=dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; drug from &nbsp;<math style="vertical-align: 0px">t=a</math>&nbsp; to &nbsp;<math style="vertical-align: 0px">t=b.</math>  
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 19: Line 25:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using integration by parts.
+
|To calculate the total reaction to the drug from &nbsp;<math style="vertical-align: -1px">t=1</math>&nbsp; to &nbsp;<math style="vertical-align: -4px">t=6,</math>
 
|-
 
|-
|Let <math style="vertical-align: -6px">u=\sin(\ln x)</math> and <math style="vertical-align: -1px">dv=dx.</math> Then, <math style="vertical-align: -14px">du=\cos(\ln x)\frac{1}{x}dx</math> and <math style="vertical-align: -1px">v=x.</math>
+
|we need to calculate
|-
 
|Therefore, we get
 
 
|-
 
|-
 
|
 
|
::<math>\int \sin (\ln x)~dx=x\sin(\ln x)-\int \cos(\ln x)~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\int_1^6 r'(t)~dt=\int_1^6 2t^2e^{-t}~dt.</math>
 
|}
 
|}
  
Line 32: Line 36:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we need to use integration by parts again.  
+
|We proceed using integration by parts.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: 0px">u=2t^2</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-t}dt.</math>
 
|-
 
|-
|Let <math style="vertical-align: -6px">u=\cos(\ln x)</math> and <math style="vertical-align: -1px">dv=dx.</math> Then, <math style="vertical-align: -14px">du=-\sin(\ln x)\frac{1}{x}dx</math> and <math style="vertical-align: -1px">v=x.</math>  
+
|Then, &nbsp;<math style="vertical-align: -1px">du=4t~dt</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=-e^{-t}.</math>
 
|-
 
|-
|Therfore, we get
+
|Then, we have
 
|-
 
|-
|
+
|&nbsp;&nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int_1^62t^2e^{-t}~dt=\left. -2t^2e^{-t}\right|_1^6+\int_1^6 4te^{-t}~dt.</math>
::<math>\begin{array}{rcl}
 
\displaystyle{\int \sin (\ln x)~dx} & = & \displaystyle{x\sin(\ln x)-\bigg(x\cos(\ln x)+\int \sin(\ln x)~dx\bigg)}\\
 
&&\\
 
& = & \displaystyle{x\sin(\ln x)-x\cos(\ln x)-\int \sin(\ln x)~dx.}\\
 
\end{array}</math>
 
 
|}
 
|}
  
Line 49: Line 50:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
|Notice that the integral on the right of the last equation is the same integral that we had at the beginning.
+
|Now, we need to use integration by parts again.  
 
|-
 
|-
|So, if we add the integral on the right to the other side of the equation, we get
+
|Let &nbsp;<math style="vertical-align: 0px">u=4t</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">dv=e^{-t}dt.</math>
 
|-
 
|-
|
+
|Then, &nbsp;<math style="vertical-align: -1px">du=4dt</math>&nbsp; and &nbsp;<math style="vertical-align: 0px">v=-e^{-t}.</math>
::<math>2\int \sin(\ln x)~dx=x\sin(\ln x)-x\cos(\ln x).</math>
 
 
|-
 
|-
|Now, we divide both sides by 2 to get  
+
|Thus, we get
 
|-
 
|-
 
|
 
|
::<math>\int \sin(\ln x)~dx=\frac{x\sin(\ln x)}{2}-\frac{x\cos(\ln x)}{2}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
|-
+
\displaystyle{\int_1^62t^2e^{-t}~dt} & = & \displaystyle{\left. -2t^2e^{-t}-4te^{-t}\right|_1^6+\int_1^6 4e^{-t}}\\
|Thus, the final answer is
+
&&\\
|-
+
& = & \displaystyle{\left. -2t^2e^{-t}-4te^{-t}-4e^{-t}\right|_1^6}\\
|
+
&&\\
::<math>\int \sin(\ln x)~dx=\frac{x}{2}(\sin(\ln x)-\cos(\ln x))+C.</math>
+
& = & \displaystyle{-2(6)^2e^{-6}-4(6)e^{-6}-4e^{-6}}-(-2(1)^2e^{-1}-4(1)e^{-1}-4e^{-1}) \\
 +
&&\\
 +
& = & \displaystyle{\frac{-100+10e^5}{e^6}.}
 +
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; <math>\frac{x}{2}(\sin(\ln x)-\cos(\ln x))+C</math>
+
|&nbsp; &nbsp; &nbsp;&nbsp; <math>\frac{-100+10e^5}{e^6}</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Revision as of 11:20, 9 April 2017

The rate of reaction to a drug is given by:

where    is the number of hours since the drug was administered.

Find the total reaction to the drug from    to  


Foundations:  
If we calculate    what are we calculating?

        We are calculating    This is the total reaction to the

        drug from    to  


Solution:

Step 1:  
To calculate the total reaction to the drug from    to  
we need to calculate

       

Step 2:  
We proceed using integration by parts.
Let    and  
Then,    and  
Then, we have
      
Step 3:  
Now, we need to use integration by parts again.
Let    and  
Then,    and  
Thus, we get

       


Final Answer:  
      

Return to Sample Exam